Assessing Wärtsilä's exhaust gas abatement solution: Life cycle assessment of a SOx scrubber system - Laatikainen, Lauri Samuel (My University, 2024)
Wärtsilä offers competent technical solutions for complying with the sulphur content regulations set by the IMO. Wärtsilä’s exhaust gas cleaning systems are a viable option for ship owners and operators that prefer to continue operating their vessels with fuels with a sulphur content of over 0,5% m/m. As the number of environmental regulations on maritime traffic and related industries is likely to increase in the near future, a proactive approach can yield beneficial results for companies looking to offset the impact of potential future restrictions. In this study, a life cycle assessment of a Wärtsilä V-SOx hybrid scrubber system was conducted. The used methodology followed the principles and framework demonstrated in the ISO 14040 standard. The main objective of the study was to generate information about the environmental impacts of the scrubber system throughout its life cycle. The results were to be used to initiate the process of developing environmental KPIs to monitor and improve Wärtsilä’s environmental performance. Also, the study was conducted to support Wärtsilä’s efforts to decarbonize its own operations by 2030. The studied scrubber system was installed on a tanker vessel in 2019. The life cycle inventory for the LCA was built using data from Wärtsilä’s internal databases, scientific literature and documentation provided by the customer. The impacts were assessed with the ILCD 2011 midpoint+ method, which contains the impact categories recommended by the European Joint Research Centre. Most of the potential environmental impacts occurred during the operational phase. The raw material extraction & manufacturing of components phase produced the second highest potential impacts. These phases combined produced more than 98% of the potential impacts in each measured impact category except for the freshwater ecotoxicity category. The system had been operated mostly in open loop mode, and therefore an additional scenario analysis was conducted to get an overview of the potential environmental impacts of operating the system in closed loop mode. Although contributing less to marine eutrophication, closed loop operation was found to produce a significant number of indirect impacts in all the other impact categories. For example, the production of sodium hydroxide used in closed loop operation multiplied the potential CO2 emissions in both additional scenarios. In addition to direct environmental impacts, the LCA produced significant insight to the indirect impacts behind the processes that are connected to the system’s life cycle. As the responsibility of mitigating environmental burden through regulations will likely extend to affect more operators in supply chains, Wärtsilä is taking proactive steps to find various ways of improving its environmental performance.

Wärtsilä tarjoaa tehokkaita teknisiä ratkaisuja IMO:n asettamien rikkipitoisuusmääräysten noudattamiseen. Wärtsilän pakokaasunpuhdistusjärjestelmät ovat pätevä vaihtoehto laivanomistajille ja operaattoreille, jotka haluavat jatkaa alustensa toimintaa polttoaineilla, joiden rikkipitoisuus on yli 0,5% m/m. Koska meriliikennettä ja siihen liittyviä toimialoja koskevien ympäristömääräysten määrä todennäköisesti lisääntyy lähitulevaisuudessa, ennakoiva lähestymistapa voi tuottaa hyödyllisiä tuloksia yrityksille, jotka haluavat lieventää mahdollisten tulevien määräysten vaikutuksia. Tässä työssä suoritettiin elinkaariarviointi Wärtsilän V-SOx hybridijärjestelmälle. Käytetty metodologia noudatti ISO 14040 – standardin toimintaperiaatteita ja viitekehystä. Tutkimuksen päätavoitteena oli tuottaa tietoa järjestelmän ympäristövaikutuksista koko sen elinkaaren ajalta. Tuloksia käytettiin käynnistämään ympäristöindikaattoreiden kehitysprosessi, joiden tarkoituksena on seurata ja auttaa parantamaan Wärtsilän ympäristötehokkuutta. Työn tarkoituksena oli myös tukea Wärtsilän vuodelle 2030 asettamaa hiilineutraalisuustavoitetta. Tutkimuksen kohteena ollut pesurijärjestelmä asennettiin erääseen säiliöalukseen vuonna 2019. Elinkaari-inventaario rakennettiin käyttäen Wärtsilän sisäisiä tietokantoja, tieteellistä kirjallisuutta ja asiakkaan toimittamaa dokumentaatiota. Ympäristövaikutukset arvioitiin ILCD 2011 midpoint+ menetelmällä, joka sisältää Euroopan yhteisen tutkimuskeskuksen suosittelemat vaikutusluokat. Valtaosa potentiaalisista ympäristövaikutuksista syntyi käyttövaiheen aikana. Raaka-aineiden louhinta & komponenttien valmistusvaihe tuotti toiseksi eniten potentiaalisia ympäristövaikutuksia. Nämä vaiheet tuottivat makean veden ekomyrkyllisyysluokkaa lukuunottamatta yli 98% potentiaalisista vaikutuksista jokaisessa mitatussa vaikutusluokassa. Järjestelmää oli käytetty pääosin avoimen kierron tilassa, minkä vuoksi suoritettiin ylimääräinen skenaarioanalyysi yleiskuvan saamiseksi suljetun kierron käytön mahdollisista ympäristövaikutuksista. Vaikka suljetun kierron toiminnalla oli vähemmän vaikutusta merialueiden rehevöitymiseen, sen havaittiin aiheuttavan huomattavan määrän epäsuoria vaikutuksia kaikissa muissa mitatuissa vaikutusluokissa. Suljetun kierron operaatiossa käytettävän natriumhydroksidin tuotanto esimerkiksi moninkertaisti potentiaaliset CO2 päästöt molemmissa lisäskenaarioissa. Suorien ympäristövaikutusten lisäksi työ tuotti merkittävää näkemystä järjestelmän elinkaareen liittyvien prosessien taustalla olevista välillisistä vaikutuksista. Koska vastuu ympäristöstä tulee todennäköisesti koskettamaan yhä useampaa toimijaa tulevaisuudessa, Wärtsilä tekee ennakoivia toimenpiteitä löytääkseen erilaisia tapoja parantaa ympäristötehokkuuttaan.
Keywords: ympäristövaikutukset; päästöt; elinkaari; pakokaasut; elinkaariarviointi; telakkateollisuus; merenkulku; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics